NOTCH1, SF3B1, and TP53 mutations in fludarabine-refractory CLL patients treated with alemtuzumab: results from the CLL2H trial of the GCLLSG - Schnaiter, Andrea Barbara; Paschka, Peter; Rossi, Marianna; Zenz, Thorsten; Bühler, Andreas; Winkler, Dirk; Cazzola, Mario; Döhner, Konstanze; Edelmann, Jennifer; Mertens, Daniel; Kless, Sabrina; Mack, Silja; et al. (Blood, 2013)
We studied the incidences, associations, and prognostic roles of NOTCH1 and SF3B1 mutations (NOTCH1mut, SF3B1mut) as compared with TP53mut in fludarabine-refractory chronic lymphocytic leukemia (CLL) patients treated with alemtuzumab in the CLL2H trial. We found NOTCH1mut, SF3B1mut, and TP53mut in 13.4%, 17.5%, and 37.4% of patients, respectively. NOTCH1mut and SF3B1mut were mutually exclusive, whereas TP53mut were evenly distributed within both subgroups. Apart from correlation of SF3B1mut with 11q deletion (P = .029), there were no other significant associations of the mutations with any baseline characteristics or response rates. However, NOTCH1mut cases had a significantly longer progression-free survival (PFS) compared with wild-type cases (15.47 vs 6.74 months; P = .025), although there was no significant difference with overall survival (OS). SF3B1mut had no significant impact on PFS and OS. In multivariable analyses, NOTCH1mut was identified as an independent favorable marker for PFS. This clinical trial is registered at www.clinicaltrials.gov as #NCT00274976.
Gesehen am 12.07.2021